A physiologically based pharmacokinetic model for V937 oncolytic virus in mice - Peribañez-Dominguez, Sara; Parra-Guillen, Zinnia P.; Freshwater, Tomoko; Troconiz, Iñaki F. (Frontiers in Pharmacology, 2023)
Introduction: Oncolytic viruses (OVs) represent a novel therapeutic strategy in oncology due to their capability to selectively infect and replicate in cancer cells, triggering a direct and/or immune induced tumor lysis. However, the mechanisms governing OV pharmacokinetics (PK) are still poorly understood. This work aims to develop a physiologically-based pharmacokinetic (PBPK) model of the novel OV, V937, in non-tumor bearing mice to get a quantitative understanding of its elimination and tissue uptake processes.Model development was performed using data obtained from 60 mice. Viral levels were quantified from 8 tissues after a single intravenous V937 dose. An external dataset was used for model validation. This test set included multiple dose experiments with different routes of administration. V937 distribution in each organ was described using a physiological structure based on mouse specific organ blood flows and volumes. Analyses were performed using the non-linear mixed effects approach with NONMEM 7.4.Viral levels showed a drop from 10 8 to 10 5 copies/µg RNA at day 1 in blood, reflected in a high estimate of total clearance (18.2 mL/h). A well-stirred model provided an adequate description for all organs except muscle and heart, where a saturable uptake process improved data description. The highest number of viral copies were observed in the brain, lymph node, kidney, liver, lung, and spleen on the first day after injection. On the other hand, the maximum amount of viral copies in the heart, muscle, and pancreas occurred three days after administration. This is a provisional file, not the final typeset article Conclusions: To the best of our knowledge, this is the first PBPK model developed to characterize OV biodistribution, representing a relevant source of quantitative knowledge regarding the in vivo behavior of OVs. This model can be further expanded by adding a tumor compartment, where OV could replicate.